Analysis of the use of discourse deixis on antagonistic actions in ‘Pourris Gâtes’ - Arif Adi Prakoso; Iim Siti Karimah; Dudung Gumilar (Universitas Cokroaminoto Palopo, 2024)
This research examines the use of discourse deixis in expressive illocutionary acts of sadness, joy, anger, disgust, fear, and surprise, as articulated by Juan Carlos in the film “pourris gâtes” The central plot of the film revolves around Francis Bartek's endeavor to teach his children about maturity by feigning poverty. However, this is discovered by Juan Carlos, who is Stella's boyfriend, and he aims to exploit the wealth of Francis' children. The dialogue between Juan Carlos, Francis Bartek, Phillippe, Stella, and Alexandre is analyzed using Levinson's theory, which emphasizes that discourse deixis involves the use of temporal, spatial, and demonstrative words. This research explains how the involvement of discourse deixis in expressive illocutionary acts can support the ‘telling’ and ‘showing’ methods in characterizing Juan Carlos’s antagonism through ineffective sentences and violations of the cooperative principle carried out by Juan Carlos.